The predictive value of the ratio of multi-dimensional inflammatory biomarkers in pediatric diseases from the perspective of pro-inflammatory/anti-inflammatory balance: a systematic review - Chen, Xuepeng; Ding, Bo; Shen, Zixuan; Han, Weicheng; Li, Yi; Xie, Yilu; Wang, Kaijing; Wang, Yazhou (Translational Pediatrics; Vol 15, No 5 (May 31, 2026): Translational Pediatrics, 2026)
Imbalance of immune homeostasis, particularly the dysregulation of pro-inflammatory/anti-inflammatory balance, is a core pathological mechanism in many acute and chronic pediatric diseases. Traditional single inflammatory biomarkers have limitations in disease prediction, clinical evaluation, and prognostic stratification, as they cannot reflect the overall dynamic balance of the immune network. This systematic review aimed to evaluate the predictive value of multi‑dimensional inflammatory biomarker ratios centered on pro‑inflammatory/anti‑inflammatory balance in pediatric inflammatory diseases, and to clarify their classification and clinical application strategies.